GE_GERICHTE C/13794/2017 vom 23. April 2019 - GE Cour de justice (2019)
INTERPRÉTATION(SENS GÉNÉRAL) ; HEURES DE TRAVAIL SUPPLÉMENTAIRES ; FARDEAU DE LA PREUVE ; DEVOIR PROFESSIONNEL | CO.18.al1; CO.321c.al1+3; CC.8; CO.42.al2